The use of tourism brochure as media in improving students’ vocabulary mastery - Dwita Rama Ayuningrum (U-Jet Unila Journal of English Language Teaching, 2024)
This research aimed to find out whether there was a statistically significant increase of students’ vocabulary improvement between pretest and posttest after the implementation of tourism brochure as media. The research was quantitative research using one group pretest and posttest design. The samples of this research were thirty four students in class XI.-1, majoring in tourism at SMKN 1 Kalianda in the academic year 2022/2023. The data were collected using pretest and posttest of vocabulary test. In order to analyze the result, Paired Sample T-test was used to test the hypothesis. It was proven by the increase of the students’ mean score in the pretest was 59.41 and the students’ mean score in the posttest was 78.82. It showed that the gain of students’ improvement was 19.41. The result showed that there was a statistically significant increase of students’ vocabulary with the significant level (0.00<0.05) and the t-value (11.184) was higher than t-table (2.0345). This suggests that teaching vocabulary using tourism brochure facilitates students to improve their vocabulary mastery.